Solanum virginianum mediated green nanoparticles to control dental pathogens - Samrin Barkath Akbar Basha; Ranjani Soundhararajan; Hemalatha Srinivasan (Discover Applied Sciences)
Abstract In recent years, nanotechnology has set a prominent advancement in the research fields particularly in the synthesis of nanomaterials, nanoparticles, nanoformulation, nanoemulsion etc. Nanotechnology has a wide range of applications in dentistry as an antibacterial agent, dental materials, periodontal pockets, photodynamic therapy and many more. Post-endodontic therapy pain and infection were more frequently detected in endodontic treatment failure cases. Dental caries most commonly referred to as cavities or tooth decay, is a serious worldwide health concern that affects people of all age groups and socioeconomic backgrounds. With the rise in antimicrobial resistance the need for alternatives is the need of the hour to treat pathogens causing dental infections. Green nanoparticles with potent antimicrobial property can be utilized to control drug resistant dental pathogens. In this study, the green synthesis of silver nanoparticles (SVAgNPs) was achieved by using Solanum virginianum fruit extract as capping and reducing agent. Characterization techniques confirmed the size, shape and stability of SVAgNPs as spherical in shape with the size ranging from 50 to 90 nm by using FESEM analysis. The hydrodynamic size of SVAgNPs was observed as 177 d.nm. Surface charge of SVAgNPs was measured as − 0.627 mV confirming its stability. The toxicity study shows that SVAgNPs was not toxic for plants and animals. Rather, SVAgNPs promotes plant growth and did not show any abnormalities in Zebrafish models. The antibacterial assays confirmed that the nanoparticles have potent antibacterial and antibiofilm properties in dental pathogens including Enterococcus faecalis and Streptococcus mutans. Based on exploring the mechanism of action of nanoparticles it was observed that SVAgNPs targets dental pathogens more effectively than the antibiotics by inducing the leakage of cellular macromolecules and causing oxidative stress to the bacterial cells. This is the first report on SVAgNPs incorporated dentures controlling the biofilm formation of Enterococcus faecalis and Streptococcus mutans more effectively than ampicillin. Overall, this work highlights the capability of SVAgNPs as potent antibacterial and antibiofilm agents to control dental pathogens. In future, SVAgNPs incorporated oral hygiene, and dentistry products can be developed for the benefit of dental care.